Patterns of Abundance of fish larvae, fish eggs, decapod shrimp larvae, and cubomedusae in two coastal areas in Iligan Bay, Northern Mindanao, Philippines - Metillo, Ephrime; Dajao, Samson Jr. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Two adjacent inshore areas in lligan Bay were sampled every month for 13 months from October 1998 to October 1999 to determine spatio-temporal abundance patterns of fish larvae, fish eggs, decapod shrimp larvae, and cubomedusae. In all four categories, abundance varies between months but less so between sites. The monthly variations in peaks of abundance conform for the three (3)-month seasons (March-April-May = dry hot, June-July-August = wet-hot, September-October-November = wet-cold, December-January-February = dry cold) within ayear and the dominant northeast and southwest monsoonal patterns. Variability in abundance of the four zooplanktonic groups correlate with salinity, water temperature and depth. The El Nino phenomenon incidentally appears to contribute to the variability. Therefore, the present study provides evidence to the growing knowledge that patterns do exist particularly in tropical planktonic communities that are important to tropical fisheries.